The evolution of islam-culture fusion, identity, islamic resurgence and current challenges in the Malay life - Musa, Hashim (Faculty of Computer Science & Information Technology, University of Malaya, 2009)
The Muslims in Malaysia makes up the majority of the population that is 60%, while the Buddhists 19%, Christians 9%, Hindus 6.3%, Chinese traditional religious believers 4.5% and the rest are either animists or sans religion. Thus Islam forms the definitive colouring or cultural landscape of Malaysia, with other religions and cultural elements adding to its overall patterns. The worldview, doctrinal belief and faith, ethical and moral values of the Malays being all Muslims, are based on Islamic teaching. However in certain cultural practices, a cultural fusion of indigenous and Indian elements can be traced due to its historical experiences, especially in such traditional rituals of healings, pacification offerings and cleansing, and also in the installation ceremonies of the rulers and the King, the shadow play performances, marriages and rites-de-passage ceremonies, etc. The colonization of the Western powers in the Malay world in the 16th century, have tremendous effect upon the Malays with their agenda of 3 Gs (gold, glory, Gospel), depriving them of their political, economic and cultural dominance in their own lands. However, the combination of Islamic revivalism and nationalism in the beginning of the 20th century became the basis of their struggle for independence, culminating in the formation of United Malay National Organization (UMNO) in 1946. In 1957, after several negotiations between the then leader of UMNO Tunku Abdul Rahman with the British government, and supported by the leaders of the Chinese organization (MCA) and the Indian organization (MIC), Malaysia obtained its independent. The post independent era, however saw new challenges in the form of racial tension, conflicts and violence culminating in the 13th May 1969 riots that led to the declaration of Emergency Rule. Consequently several proactive measures were taken by the government, the major ones were the formation of the National Front a coalition party that brought together major political parties representing main ethnics, regional and interest groups, the formation of National Unity Department, and the formation National Ideology the Rukun Negara, to instils national integration and unity among the multi-ethnic-cultural-religious population. However, the gravest challenge now faced by the Malays and Muslims as a whole, is the negative perception and the lowest possible image of them in the eyes of the world, perceiving them as people who are intolerant, violent, bigoted and generally disrespectful towards other religions, and worst, as terrorists threatening world security and peace. This article proposes some strategies to resolve these problems